Acute Blepharitis: Diagnose and Management - Vania Widyadhari Damayanti; Rani Himayani (Medula, 2023)
Blepharitis is an eye disorder that indicates inflammation at the edges of the palpebrae. Blepharitis can be divided into acute and chronic. Causes of acute blepharitis include bacterial, viral, or allergic reactions. Clinical manifestations that may appear include itching, burning, crusting, tearing, blurred vision, and foreign body sensation. No special diagnostic tests are needed other than a history and physical examination. Management in dealing with acute blepharitis is by keeping the eyes clean, warm and wet compresses, administering antibiotic ointments, administering topical corticosteroids. A diet that increases omega-3s and reduces omega-6s can also help with blepharitis symptoms. Food sources that contain omega-3s include sprouts, breast milk, and certain fish oils. Meanwhile food sources of omega-6 are meat, eggs, poultry, cereals, avocados, sunflower oil, corn oil, cottonseed oil, linseed oil, vegetable oils, margarine, sunflower seeds, pumpkin seeds, walnut seeds, soybeans, cashews, and other nuts.